Pengembangan Media Pembelajaran Vidio Animasi Berbasis Aplikasi Canva Pada Materi IPAS Bagian Tubuh Tumbuhan Kelas IV SDN 10 Muara Sugihan - Khanifah, Niken Asih; Arni, Yusni; Pratiwi, Marina; Anggrina, Ulan Despi (ALACRITY : Journal of Education, 2024)
Learning media is a component that has an important role in the implementation of learning. The problems that are often encountered are the lack of use of learning media during learning and also the use of learning resources which is still lacking (Ergantara & Sari, 2023). This research aims to develop animated video learning media based on the Canva application on science content material on plant body parts for class IV SDN 10 Muara Sugihan. The lack of learning media that attracts students' interest is the impetus for conducting this research. Students have characters who enjoy playing games, watching YouTube, TikTok and even making TikTok. The solution that educators can take is to introduce animated videos into the learning process. The aim of this research is to produce animated video learning media that is valid, practical and effective. This research uses the Research and Development (R&D) research method with a 4-D paradigm consisting of the stages of definition, design, development and distribution.